2005
DOI: 10.1111/j.1600-0420.2005.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Dominant optic atrophy: correlation between clinical and molecular genetic studies

Abstract: ABSTRACT.Purpose: To assess the clinical picture and molecular genetics of 14 Finnish families with dominant optic atrophy (DOA). Methods: The clinical status of family members was based on the assessment of visual acuity, colour vision, visual fields and optic nerve appearance; 31 individuals were affected, two suspect and 21 unaffected. A total of 30 coding exons and exonÀ intron boundaries of the OPA1 gene were sequenced in order to detect mutations. Results: Half the patients were diagnosed at the age of £… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 39 publications
1
38
0
1
Order By: Relevance
“…15 Because the majority of OPA1 mutations truncate or disrupt the normal gene product and thus represent null alleles, haploinsufficiency has been cited as the major mechanism of action. 2,3,16 However, there are a number of pathogenic missense mutations and an example of semi-dominant inheritance in an OPA1 compound heterozygote, suggesting that different pathways of altered OPA1 protein function or production can lead to ADOA. 2,15,16 OPA1 mutations account for roughly one-third to twothirds of ADOA cases, and this locus heterogeneity may be responsible for the considerable phenotypic heterogeneity seen in ADOA.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…15 Because the majority of OPA1 mutations truncate or disrupt the normal gene product and thus represent null alleles, haploinsufficiency has been cited as the major mechanism of action. 2,3,16 However, there are a number of pathogenic missense mutations and an example of semi-dominant inheritance in an OPA1 compound heterozygote, suggesting that different pathways of altered OPA1 protein function or production can lead to ADOA. 2,15,16 OPA1 mutations account for roughly one-third to twothirds of ADOA cases, and this locus heterogeneity may be responsible for the considerable phenotypic heterogeneity seen in ADOA.…”
mentioning
confidence: 99%
“…3 Although a deleterious mutation can occur throughout the gene, Thistleton et al (2002) have identified three general regions where mutations have loosely clustered: the N-terminal leader sequence (exons 1-2) domain, the GTPase (exons [8][9][10][11][12][13][14][15][16] domain, and the C-terminus (exons [27][28]. 15 Because the majority of OPA1 mutations truncate or disrupt the normal gene product and thus represent null alleles, haploinsufficiency has been cited as the major mechanism of action.…”
mentioning
confidence: 99%
See 3 more Smart Citations